The Relationship between Stress Levels and Cardiovascular Health Parameters in Students of the Faculty of Medicine, Imelda University, Medan - Irpan Efendi Rambe; Ibnu Arizona Siregar; Nurul Sulviani; Inawaty; Meldawati (Benih : Journal of Midwifery, 2025)
Cardiovascular health is a critical aspect of overall well-being, particularly among medical students who often experience high levels of academic stress. Persistent stress has been shown to influence autonomic function, elevate blood pressure, and disrupt heart rate variability (HRV), thereby increasing the risk of early cardiovascular dysfunction. This study aims to examine the relationship between stress levels and cardiovascular health parameters—specifically blood pressure, resting heart rate, and body mass index (BMI)—among medical students at Universitas Imelda Medan. Using a cross-sectional design, data were collected through standardized stress questionnaires and physiological measurements. The findings are expected to demonstrate a significant association between higher stress levels and adverse cardiovascular indicators. Understanding this relationship may contribute to the development of preventive strategies and stress management interventions within medical education settings. Ultimately, this study highlights the importance of promoting mental well-being and healthy lifestyle practices to protect cardiovascular health in young adult populations.